Evaluation of Investment Projects in Photovoltaic Solar Energy using the DNPV Methodology - MartÃnez-Ruiz, Yessenia; Manotas-Duque, Diego Fernando; RamÃrez-Malule, Howard (International Journal of Energy Economics and Policy, 2020)
The evaluation of investment projects has been carried out mainly through the analysis of Discounted Cash Flow (DCF), whose financial feasibility measures have been based fundamentally on approaches such as the Net Present Value (NPV) and the Internal Rate of Return (IRR), which are widely discussed in the field of energy project valuation. Despite this, the classical methods have a limitation when perceiving relevant characteristics for decision-making in high-risk investments, such as the uncertainty of the cash flows and the quantification of risk. An alternative to the use of these methods is the technique known as Decoupled Net Present Value (DNPV), which decouples the risk associated with the project from the value of money over time. This valuation methodology was applied to a photovoltaic solar energy self-generation project in Colombia. In this study, the results obtained through the DNPV was equivalent to 2.3-fold the value obtained by means of NPV. Thus, many renewable energy projects can become undervalued since traditional methods mistakenly associated a discount rate that includes a very high risk premium and that in many occasions it is more related to the sources of financing of the project instead of representing the risk component that it has. Keywords: Decoupled net present value (DNPV), Renewable energy projects, Solar energy investments JEL Classifications: Q2, Q4 DOI: https://doi.org/10.32479/ijeep.10577